(untitled) (Global Journals of Research in Engineering, 2023)
The worldwide use of information and communications technology ICT equipment and other electronic equipment is growing There is growing amount of equipment that becomes waste after its time in use This growth is expected to accelerate since equipment lifetime decreases with time and growing consumption As a result e-waste is one of the fastest-growing waste streams globally The United Nations University UNU calculates in its second Global E-waste Monitor 44 7 million metric tonnes Mt of e-waste were generated globally in 2016 The objective of the study was to develop a framework for improving e-waste management at the College of Engineering Design Art and Technology CEDAT This was achieved by breaking it down into specific objectives and these included the establishment of the policy and procedures being used in e-waste management at CEDAT the determination of the effectiveness of the e-waste management practices at CEDAT the establishment of the critical challenges constraining e-waste management at the College development of a framework for e-waste management The study population was 80 respondents from which a sample of 69 respondents was selected using simple and purposive sampling techniques This research was carried out to investigate the problem of e-waste and come up with a framework to improve e-waste management The study reviewed the e-waste regulatory framework used at the college and then collected data which was used to come up with a framework The study also established that weak policy and regulatory framework lack of proper infrastructure improper disposal of e-waste and a general lack of awareness of the e-waste and the magnitude of the problem are the critical challenges of e-waste management In order to appropriately address the issue the policy and regulatory framework should be updated localized and strengthened It will be helpful to launch awareness campaigns create the necessary infrastructure and conduct significant research to determine the scope and severity of the issues The study suggests a framework for e-waste improvement